Jurisdição constitucional e reforma política: limites e possibilidades de atuação do Supremo Tribunal Federal - Rafael Costa de Souza (2017)
With the expansion of judicial review and the phenomenon of the judicialization of politics, the Judiciary has faced problems of political life that historically were solved by the Legislative and Executive Powers. In the Brazilian experience, the Federal Supreme Court has adjudicated questions about political reforms, such as campaign funding, barrier clause, or partisan allegiance. Whenever Constitutional Courts are faced with issues that typically concern the majoritarian political process, the classic dilemma of the "countermajoritarian difficulty" resurfaces and the discussion on the democratic legitimacy of judicial review. After going through a long period of enthusiasm, the expansion of constitutional jurisdiction has been reviewed by contemporary constitutional theory. The contributions of the new critics to the judicial supremacy have demonstrated the need to rethink the theoretical model of justification of the constitutional review. The problem becomes more specific when it comes to the structuring nucleus of the democratic process, such as political reform. In this context, the dissertation analyzes the limits and possibilities of action of the Federal Supreme Court in matters of political reform in light of contemporary theories critical of judicial supremacy.